Resituating the Sketch/ Bitacora in the Production of Knowledge and Anthropological Meaning - Cortés Severino, Catalina (2017)
The principle objective of this article is to situate the analysis of the “bodily turn” within the study of “the visual”. This locates the researcher not as an objective observer at a distance but instead in another way of looking at and relating with the world. Instead of something “out there” the world is seen as something that affects us and that we also shape through our own perceptions. In this sense, the body is the axis that articulates, recognizes and repositions physical bodies as the fundamental axis through which anthropological research can be renewed in our continent. From these points of departure, the purpose of this article is to illustrate, articulate and share some of my experiences in the “how to” of ethnographic research on everyday life as a narrative and visual practice.